A few words about brochure "Death from graves" - Gabriela Frischke (Kazimierz Wielki University, 2017)
In the second half of the 18th century, attention was paid to the problem of harmful air arising from burials in churches and in urban cemeteries. For several years, in many countries, special regulations have been issued banning such funerals and ordering to transfer dead bodies to new cemeteries away from human homes. This article deals with the brochure "Death from graves" of an unknown author, published in 1781 in Lviv. The text is bringing up a lot of health problems associated with the poisoned air coming from graves in the city and fits into the polemics of the time.